Impact on survival of intensive follow up after curative resection for colorectal cancer: systematic review and meta-analysis of randomised trials - Renehan, Andrew G (BMJ Publishing Group, 2002)
OBJECTIVE: To review the evidence from clinical trials of follow up of patients after curative resection for colorectal cancer. DESIGN: Systematic review and meta-analysis of randomised controlled trials of intensive compared with control follow up. MAIN OUTCOME MEASURES: All cause mortality at five years (primary outcome). Rates of recurrence of intraluminal, local, and metastatic disease and metachronous (second colorectal primary) cancers (secondary outcomes). RESULTS: Five trials, which included 1342 patients, met the inclusion criteria. Intensive follow up was associated with a reduction in all cause mortality (combined risk ratio 0.81, 95% confidence interval 0.70 to 0.94, P=0.007). The effect was most pronounced in the four extramural detection trials that used computed tomography and frequent measurements of serum carcinoembryonic antigen (risk ratio 0.73, 0.60 to 0.89, P=0.002). Intensive follow up was associated with significantly earlier detection of all recurrences (difference in means 8.5 months, 7.6 to 9.4 months, P<0.001) and an increased detection rate for isolated local recurrences (risk ratio 1.61, 1.12 to 2.32, P=0.011). CONCLUSIONS: Intensive follow up after curative resection for colorectal cancer improves survival. Large trials are required to identify which components of intensive follow up are most beneficial.